Structure and soft magnetic properties of FINEMET type alloys: Fe73.5Si13.5Nb3 − xMoxB9Cu1 (x = 1.5, 2) - Silveyra, Josefina María (2010)
FINEMET type ribbons (Fe73.5Si13.5Nb3 − xMoxB9Cu1, x = 1.5, 2 at.%) were produced by the planar flow casting technique and subsequently heat treated at 823 K to induce nanocrystallization and to optimize its soft magnetic properties. The coercivity, measured by conventional fluxmetric method, resulted in HC = 0.53 ±0.10 and 0.41±0.05 A/m for x = 1.5 and 2 respectively. A correlation between magnetic properties and the amorphous and nanocrystalline phases when Nb was partially substituted with Mo was studied by means of Mössbauer spectroscopy and X-ray diffraction.